Electromyographical analysis of plyometric exercises - Simenz, C. J.; Geiser, C. E.; Leigh, D. H.; Melbye, J.; Jensen, R. L.; Ebben, W. P. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to evaluate integrated electromyographic (IEMG) activity of the quadriceps (Q), hamstring (H), and gastrocnemius (G) muscle groups during the performance of 10 randomly ordered plyometric (P) exercises. Subjects included 23 adults who routinely performed P. A one way Repeated Measures ANOVA indicated QIEMG activity was significantly different (p < 0.05) across conditions. Similarly, G-IEMG was significantly different (p < 0.05) across conditions for males and subjects with vertical jumps greater than 50 cm. No significant differences (p>0.05) were found for the G-IEMG for female subjects and those with vertical jumps less than 50 cm, or for the H muscle group. Bonferonni adjusted pairwise comparisons of main effects revealed differences in IEMG between specific P exercises.